A Review of Pre-school Period via Play-based Learning — A Stepping Stone to Learning Science - Tanwar, Pramila (SCHOOL SCIENCE, 2018)
The paper underlines the importance of early childhood period as it is considered as the foundation period for all kinds of development. The author stresses that the teachers and parents should provide congenial environment to the children to explore the nature and the learning environment is enriched with the materials capable of arousing the natural curiosity of children. She concludes that children are naturally scientists. Hence, the learning environment should be simulative and enriched with natural play materials that can arouse interest of children for learning science concepts.